La cultura dels escribes i notaris de la Corona d'Aragó - Trench, Josep; Canellas, A. (Caplletra. Revista Internacional de Filologia, 2015)
This paper reviews the work of the secretaries and scribes of the Royal Catalan-Aragonese Chancellory, from the time of Peter teh Ceremonious to that of Ferdinand of Aragon. It provides brieg biobliographic information that identifies the beginnings of so-called Catalan-Aragonese Humanism, which cannot be dated before the late 14th century.